(3GdQSGdI GdMGJejI (B((3ef MceI CQSWGWGdjS hTYQ CHj GdWjH GdeJfHi(B)s - (3eMeO Hf GdMSf Hf GdeXaQ GdMGJej GdHZOGOj , CHh Ydj,J (B388 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf CNa eG CMJceJ Gdjg fahS Chdi GdfXQ hGfbGOJ Gdjg BQGA Ggd GdacQ s
(3BNQgG (B:s
(3ZGjI GdeaQW ai Sdeg cZGjI GdeaQW ai MQHg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B82 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B222 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B56s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B27 s
(3eUOQ GbJfGA GdCUd (B:s
(3eYgO OejGW (B((3ehGYX (B23) s
Keywords: (3GdCOHs